Wi-Fi network testing using an integrated Evil-Twin framework - Esser, A.; Serrão, C. (The Fifth International Conference on Internet of Things: Systems, Management and Security, IoTSMS 2018, 2018)
This work intends to present a newly developed Wi- Fi vulnerability analysis and exploitation framework with the objective of increasing Wi-Fi security. The developed framework focuses primarily on client-side vulnerabilities, currently a weak- ness on Wi-Fi connections, but can be extended to support any type of Wi-Fi attack. The framework was designed and is in- tended to be used by security auditors when performing intrusion tests on Wi-Fi networks. It can also be used as a proof-of-concept tool meant to teach and raise awareness of the risks involved when using Wi-Fi technologies. The developed framework is based on open-source software and is also available as open- source software, allowing developers to extend its functionality.